2011
DOI: 10.2478/v10201-011-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated Body Temperature on Control of Breathing

Abstract: Changes in body temperature can be evoked mainly by alterations in the peripheral temperature, or modified by shifts in the central body temperature. Two conditions can lead to abnormal elevation of body temperature: hyperthermia or fever. As regards respiratory system, exposure to heat stress is accompanied by marked alterations in breathing, especially by an increase in ventilation. Ventilation rises due to an increase in central output from hypothalamus or brainstem, an increase in peripheral output via ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…It is thought that reduced feather cover may be advantageous for thermoregulation at high T a by increasing sensible heat loss. It has been reported that body temperature changes are accompanied with marked alterations in breathing pattern (Zila & Calkovska, 2011). Increases in RR of up to 165 breaths/min were observed in broilers at 42 d of age under high temperatures (Silva et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that reduced feather cover may be advantageous for thermoregulation at high T a by increasing sensible heat loss. It has been reported that body temperature changes are accompanied with marked alterations in breathing pattern (Zila & Calkovska, 2011). Increases in RR of up to 165 breaths/min were observed in broilers at 42 d of age under high temperatures (Silva et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The RespR recorded by Samimi and Tajik () in miniature donkeys was lower than the values obtained in the current study. The relatively high RespR during the hot‐dry season compared to the cold‐dry season was apparently the result of exposure to heat, accompanied by marked alterations in respiration to increase ventilation (Zila and Calkovska ; Lenis Sanin et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The RespR recorded by Samimi and Tajik (2017) in miniature donkeys was lower than the values obtained in the current study. The relatively high RespR during the hot-dry season compared to the cold-dry season was apparently the result of exposure to heat, accompanied by marked alterations in respiration to increase ventilation (Zila and Calkovska 2011;Lenis Sanin et al 2016). The increase in mesor of RespR in the hot-dry season is in agreement with the finding of Shawaf et al (2018) in Shetland ponies, who reported that RespR was higher in the summer than the winter period in the eastern province of Saudi Arabia.…”
Section: Respr In Adult Yearling and Foal Donkeys During The Cold-dmentioning
confidence: 99%
“…In humans elevated temperatures increase ventilation (Zila and Calkovska, 2011) and therefore respiration. Plants respire more CO 2 at higher temperatures, because their internal processes intensify.…”
Section: Carbon Releasementioning
confidence: 99%